Habitat suitability for conservation translocation: The importance of considering camouflage in cryptic species. (November 2016) - Baling, Marleen; Stuart-Fox, Devi; Brunton, Dianne H.; Dale, James
Abstract: Habitat suitability is a critical aspect for the successful establishment of a translocated population. Past studies have identified multiple factors that contribute to habitat suitability, including resource availability, presence of invasive species, landscape connectivity and climate. However, visual camouflage – coloration that conceals individuals from predators or prey – is another important ecological requirement that has been largely overlooked. We provide a case study to illustrate how color patterns of a prey species can change from that of the source site following translocation. Shore skinks ( Oligosoma smithi ) were moved from a coastal sand dune ecosystem to an offshore island beach that differed in substrate and color. Within one year following release, the translocated population's color pattern variation had reduced to mostly one pattern type. The high match in color patterns between the skinks and release site (including a new substrate type) may have contributed to the observed color pattern shift. This reduced variation in color pattern implies that not all founders survived, potentially decreasing the genetic diversity in the population. Our study highlights the importance of considering a species' camouflage requirements when selecting habitat for release, not only to maximize founder survival and establishment success, but also to maintain phenotypic and genotypic diversity in the long-term. Graphical abstract: Highlights: Factors that can influence efficacy of visual camouflage: genetics, predator, and habitat. We observed effect of translocating cryptic skinks to different habitat types. Color patterns of translocated population were reduced to mainly one type within a generation. Surviving skinks had high color or pattern match to new substrate types. Selecting habitat or individuals to achieve effective camouflage can maintain phenotypic diversity.